2016
DOI: 10.3389/fpsyg.2016.00027
|View full text |Cite
|
Sign up to set email alerts
|

Filling the Silence: Reactivation, not Reconstruction

Abstract: In a self-paced reading experiment, we investigated the processing of sluicing constructions (“sluices”) whose antecedent contained a known garden-path structure in German. Results showed decreased processing times for sluices with garden-path antecedents as well as a disadvantage for antecedents with non-canonical word order downstream from the ellipsis site. A post-hoc analysis showed the garden-path advantage also to be present in the region right before the ellipsis site. While no existing account of ellip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 51 publications
4
25
1
Order By: Relevance
“…A recent study by Paape [ 1 ] investigated whether ellipsis is processed differently depending on whether the antecedent contains a temporary syntactic ambiguity or not. A German example stimulus from the study, adapted slightly in favor of brevity, is shown in (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Paape [ 1 ] investigated whether ellipsis is processed differently depending on whether the antecedent contains a temporary syntactic ambiguity or not. A German example stimulus from the study, adapted slightly in favor of brevity, is shown in (2).…”
Section: Introductionmentioning
confidence: 99%
“…In the control condition, the auxiliary bears singular marking and thus agrees with the initial noun phrase, allowing an SVO reading. In a self-paced reading experiment, Paape [ 1 ] found that reading times were increased at the second noun phrase in the OVS version of (2a) compared to the SVO version. No such effect was observed in the two additional control sentences in (2b), where the first noun phrase carries overt case marking.…”
Section: Introductionmentioning
confidence: 99%
“…This section describes how the acceptability cline observed in Experiment 1 can be captured under a memory-based account in a single structure-building architecture. A growing number of studies suggest that ellipsis is resolved in real-time by retrieving an antecedent using a cue-based retrieval mechanism (Martin & McElree 2008;Martin et al 2012;Paape 2016). Importantly, this is the exact same mechanism that has been argued to underlie many other cases of "acceptable ungrammaticalities", such as those observed for agreement, anaphora, case licensing, and negative polarity item licensing (Vasishth et al 2008;Wagers et al 2009;Dillon et al 2013;Sloggett 2013;Tanner et al 2014;Lago et al 2015;Tucker et al 2015;Parker & Phillips 2016;Patil et al 2016).…”
Section: Computational Model Of Antecedent-ellipsis Mismatchesmentioning
confidence: 90%
“…Unlike and, but evokes no expectation of parallelism between the two conjuncts, and indeed parallelism does not facilitate processing for but-conjoined sentences (Knoeferle 2014). The main goal of Experiment 2 was to investigate whether antecedent complexity effects in ellipsis processing are sensitive to task demands, as suggested by Phillips & Parker (2014) and Paape (2016). The design is inspired mainly by Swets et al (2008)'s investigation of parsing preferences for a temporary syntactic ambiguity.…”
Section: Resultsmentioning
confidence: 99%